Synthesis of Isatin-based Chalcone Derivatives and Their Activity as Antioxidants - Saputri, Yosephine Liliana Intan Danar; Cahyana, Antonius Herry; Yunarti, Rika Tri (Reaktor, 2023)
The body needs antioxidants to combat free radicals and guard against their damaging effects on healthy cells that might result in degenerative disorders. Several degenerative diseases include hypertension, heart disease, diabetes, stroke, and cancer. The human body can deal with free radical attacks caused by radiation, stress, cigarette smoke, and environmental pollution, so it requires additional external antioxidants to protect against free radical attacks. Chalcone is a compound that has an α,β-unsaturated carbonyl system, which makes chalcone compounds have biological activity. Chalcone compounds may be used in pharmacology as antioxidants, antifungals, antibacterial agents, anticancer agents, and for other biological activities. This study aims to synthesize a chalcone derivative, namely 3-(2-oxo-2-phenylethylidene)indolin-2-one and 5-chloro-3-(2-oxo-2-phenylethylidene)indolin-2-one containing a chloro substituent, as well as test the potential of these compounds as antioxidants. The reflux method of claisen-schmidt condensation of isatin and acetophenone was used to create chalcone derivatives. Spectroscopy was used to characterize the produced chemicals (UV-VIS, IR, and LCMS) and their antioxidant activity using the DPPH method. This study showed that the antioxidant activity of 3-(2-oxo-2-phenylethylidene)indolin-2-one and 5-chloro-3-(2-oxo-2-phenylethylidene)indolin-2-one compounds is very weak at low concentrations.